Reactogenicity within the first week after Sinopharm, Sputnik V, AZD1222, and COVIran Barekat vaccines: findings from the Iranian active vaccine surveillance system - Mostafa Enayatrad; Sepideh Mahdavi; Roqayeh Aliyari; Sajad Sahab-Negah; Sairan Nili; Mohammad Fereidouni; Parvin Mangolian Shahrbabaki; Alireza Ansari-Moghaddam; Abtin Heidarzadeh; Fariba Shahraki-Sanavi; Mansooreh Fateh; Hamidreza Khajeha; et al. (BMC Infectious Diseases, 2023)
Abstract Background This study aimed to evaluate the reactogenicity effects of COVID-19 vaccines, used in Iran. Methods At least 1000 people were followed up with phone calls or self-report in a mobile application within 7 days after vaccination. Local and systemic reactogenicities were reported overall and by subgroups. Results The presence of one or more local and systemic adverse effects after the first dose of vaccines was 58.9% [(95% Confidence Intervals): 57.5–60.3)] and 60.5% (59.1–61.9), respectively. These rates were reduced to 53.8% (51.2–55.0) and 50.8% (48.8–52.7) for the second dose. The most common local adverse effect reported for all vaccines was pain in the injection site. During the first week after the first dose of vaccines, the frequency of the pain for Sinopharm, AZD1222, Sputnik V, and Barekat was 35.5%, 86.0%, 77.6%, and 30.9%, respectively. The same rates after the second dose were 27.3%, 66.5%, 63.9%, and 49.0%. The most common systemic adverse effect was fatigue. In the first dose, it was 30.3% for Sinopharm, 67.4% for AZD1222, 47.6% for Sputnik V, and 17.1% for Barekat. These rates were reduced to 24.6%, 37.1%, 36.5%, and 19.5%, in the second dose of vaccines. AZD1222 had the highest local and systemic adverse effects rates. The odds ratio of local adverse effects of the AZD1222 vaccine compared to the Sinopharm vaccine were 8.73 (95% CI 6.93–10.99) in the first dose and 4.14 (95% CI 3.32–5.17) in the second dose. Barekat and Sinopharm had the lowest frequency of local and systemic adverse effects. Compared to Sinopharm, systemic adverse effects were lower after the first dose of Barekat (OR = 0.56; 95% CI 0.46–0.67). Reactogenicity events were higher in women and younger people. Prior COVID-19 infection increased the odds of adverse effects only after the first dose of vaccines. Conclusions Pain and fatigue were the most common reactogenicities of COVID-19 vaccination. Reactogenicities were less common after the second dose of the vaccines. The adverse effects of AZD1222 were greater than those of other vaccines.